﻿Tarachoptera: The extinct and enigmatic cousins of Trichoptera and Lepidoptera, with descriptions of two new species - Wolfram Mey; Wilfried Wichard (Contributions to Entomology)
Two new species of fossil Tarachoptera are described from Burmese amber and named as Tarachocelis emmarossae sp. nov. and Kinitocelis patrickmuelleri sp. nov. The new species are documented by photos and line drawings. An update of the hitherto described taxa of Tarachoptera is provided including information about the depository of type material. The phylogenetic position of Tarachoptera in the amphiesmenopteran clade is discussed. A hypothetical cladogram based on cladistic principles was constructed to demonstrate the phylogenetic relationship combining Tarachoptera, Trichoptera, and Lepidoptera. It might serve as guidance in the interpretation of fossil taxa and future discoveries.